Irradiation grafting modified fibrous membrane dressing and preparation method thereof

By introducing functional monomers of pyridine groups and quaternary ammonium salt groups on the surface of the fiber membrane dressing, and using co-irradiation technology to form a three-dimensional network structure, the problems of insufficient mechanical properties and low transdermal absorption properties of the fiber membrane dressing are solved, and better drug transmission and release effects are achieved.

CN120514899AActive Publication Date: 2025-08-22STUDY (LUOYANG) TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510717583.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-22
Estimated Expiration
2045-05-30

AI Technical Summary

Technical Problem

The existing fiber membrane dressings have insufficient mechanical properties, low transdermal absorption performance and insufficient antibacterial properties, which affect the effective release and absorption of drugs.

Method used

By introducing functional monomers of pyridine groups and quaternary ammonium salt groups, a controlled crosslinking reaction is carried out on the surface of the fiber membrane material by co-irradiation technology to form a three-dimensional network structure, which improves the swelling, wettability, mechanical properties and antibacterial properties of the fiber membrane dressing.

Benefits of technology

It significantly improves the swelling performance, wettability, mechanical properties and transdermal absorption properties of fiber membrane dressings, and enhances the drug delivery and release effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120514899A_ABST
    Figure CN120514899A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fiber membrane dressings, and particularly relates to an irradiation grafting modified fiber membrane dressing and a preparation method thereof.3-chloro-2-hydroxypropyl methacrylate and 4-pyridylacetic acid serve as starting raw materials, pyridine groups are introduced through esterification reaction, quaternary ammonium salt groups are introduced through quaternization reaction, and a novel functional monomer is prepared; and then a co-irradiation technology is utilized, and the controllable cross-linking reaction of the functional monomer, the acrylic acid and the carboxymethyl chitosan on the surface of the fiber membrane material is successfully realized by accurately controlling process parameters such as irradiation dose and time. According to the invention, the three-dimensional network structure of the membrane material is optimized, the chemical characteristics and physical morphology of the surface of the material are significantly improved, and collaborative optimization of high swelling property, antibacterial property and transdermal absorption performance is realized while the mechanical strength is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fiber membrane dressings, and particularly relates to an irradiation grafted modified fiber membrane dressing and a preparation method thereof. Background Art

[0002] Drug delivery is an effective treatment for a wide range of human diseases. Drug carrier materials, as a crucial component of drug delivery systems, are a major factor influencing drug efficacy. Therefore, the construction of suitable drug delivery vehicles is crucial. Fiber membrane dressings are a widely used carrier material in drug delivery systems, particularly in wound healing and localized drug delivery. Their unique structure and properties make them ideal for constructing drug delivery vehicles.

[0003] The patent with application number CN202010373990.9 provides a method for preparing a nanofiber membrane wound dressing. First, chitosan is modified by ginger ketone to change the ordered structure of chitosan, reduce the intermolecular hydrogen bonding effect, and improve its moisturizing ability and swelling performance. Then, the modified chitosan is mixed with silk fibroin to prepare a spinning solution, and the nanofiber membrane wound dressing is prepared by electrospinning technology. Finally, the nanofiber membrane is modified by modifiers such as tyrosine and hyaluronic acid to increase its adsorption capacity for protein and promote wound healing. Although the mixture of modified chitosan and silk fibroin improves the swelling and moisturizing properties of the nanofiber membrane, its mechanical properties are still insufficient. In actual applications, the dressing needs to have a certain mechanical strength to withstand the stretching and friction in daily activities. In addition, in the process of wound healing, preventing infection is crucial. Lack of antibacterial properties will lead to wound infection and delayed healing. The patent application number CN202010487233.4 provides a method for preparing a high-strength nanofiber membrane wound dressing. Under light stimulation conditions, the photosensitizer graphene oxide (GO) and indocyanine green (ICG) produce a photothermal effect, and the embedded drug doxorubicin can be released in a controllable manner according to the temperature. The GO@ICG / PCM / CA / PCL nanofiber membrane prepared by electrospinning technology has the potential for sustained and controlled drug release and is suitable for wound dressings. The dressing has a high specific surface area and porous properties, good air permeability, high biocompatibility, significantly improved mechanical strength, and elongation at break increased from 6% to 12%. The hydrophilicity is enhanced, the photothermal conversion performance is stable, and the near-infrared responsiveness is sensitive. Although the dressing has many advantages, its transdermal absorption performance is insufficient. Specifically, although the hydrophilicity of the nanofiber membrane is enhanced, its transdermal absorption efficiency is still low, and it cannot effectively promote the passage of drugs through the skin barrier into deep tissues. In addition, although the photothermal effect of the dressing can trigger drug release, in actual applications, the penetration depth of light stimulation is limited and may not be able to fully act on deep wounds, affecting the effective release and absorption of drugs.

[0004] As a non-thermal processing technology, low-energy electron beam (EBI) irradiation technology has significant advantages and can effectively avoid the problem of thermal degradation of cellulose and its membrane materials caused by high temperature in traditional thermal processing technology. By directly acting on the material through accelerated high-energy electrons, EBI irradiation technology can quickly trigger the active system of the material without introducing high temperature, and realize cross-linking, grafting, polymerization, cracking, curing and other reactions, thereby functionally modifying cellulose and its membrane materials. For example, in the preparation of wound dressings, EBI irradiation technology can be used to modify cellulose membrane materials to improve their mechanical properties, hydrophilicity and drug release properties, thereby preparing fiber membrane dressings with better overall performance. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a radiation grafted modified fiber membrane dressing and a preparation method thereof. First, a new functional monomer is prepared by introducing a pyridine group and a quaternary ammonium salt group, and then the co-irradiation technology is used to successfully achieve a controllable cross-linking reaction of the functional monomer, acrylic acid and carboxymethyl chitosan on the surface of the fiber membrane material by precisely controlling the irradiation dose, time and other process parameters. The present invention optimizes the three-dimensional network structure of the membrane material, and at the same time significantly improves the chemical properties and physical morphology of the material surface, thereby systematically improving the comprehensive performance of the fiber membrane dressing.

[0006] The technical solutions adopted by the present invention to achieve the above-mentioned purpose are:

[0007] A method for preparing an irradiation-grafted modified fiber membrane dressing comprises the following steps:

[0008] Step S1: 3-chloro-2-hydroxypropyl methacrylate, N,N-dimethylformamide, and p-toluenesulfonic acid are uniformly mixed, the temperature is raised to 55-65° C. under stirring, and 4-pyridineacetic acid is added. The mixture is reacted for 6-10 hours, cooled to room temperature, and the organic phase is extracted, the extraction solvent is removed, and the mixture is dried;

[0009] Step S2: Disperse the product obtained in step S1 in anhydrous ethanol under nitrogen atmosphere and stirring, raise the temperature to 70-80°C, add potassium iodide and triethylamine, react for 15-20 hours, cool to room temperature, and purify to obtain a functional monomer;

[0010] Step S3: at room temperature, uniformly mix carboxymethyl chitosan and deionized water, stir for 40-60 minutes, then sequentially add acrylic acid, functional monomer, and cross-linking agent, and continue stirring for 10-30 minutes to obtain a mixed solution; immerse the pretreated fiber membrane in the mixed solution, place it in an irradiation reaction system for irradiation treatment, and after the irradiation is completed, remove the fiber membrane, wash it, and dry it to obtain the product;

[0011] The preparation route of the functional monomer is as follows:

[0012]

[0013] The invention uses 3-chloro-2-hydroxypropyl methacrylate and 4-pyridineacetic acid as starting materials, undergoes an esterification reaction under the catalytic action of p-toluenesulfonic acid, and then undergoes a quaternization reaction with triethylamine under the action of potassium iodide to obtain a functional monomer. A quaternary ammonium salt group, a pyridine group, and an acrylate group are introduced into the molecular structure of the functional monomer by a two-step method. Finally, the functional monomer, acrylic acid, and carboxymethyl chitosan are used as raw materials, and a cross-linking polymerization reaction is carried out on the surface of a fiber membrane material by a co-irradiation method to obtain an irradiation-grafted modified fiber membrane dressing.

[0014] In order to reduce by-products and improve reaction efficiency during the preparation of functional monomers, the molar ratio of 3-chloro-2-hydroxypropyl methacrylate, p-toluenesulfonic acid, and 4-pyridineacetic acid in step S1 is 1.1:0.01-0.02:0.8-1.0, and the mass volume ratio of 3-chloro-2-hydroxypropyl methacrylate and N,N-dimethylformamide is 0.15-0.20 g / mL; in step S2, the molar ratio of the product obtained in step S1, potassium iodide, and triethylamine is 0.9:0.22-0.28:1.2-1.4, and the amount of the product obtained in step S1 added to the anhydrous ethanol is 0.2-0.4 g / mL.

[0015] Taking into account the significant influence of the raw material ratio on the viscosity of the reaction system, and the influence of different monomer concentrations on the grafting rate and thus the product performance, the optimization results show that the mass ratio of acrylic acid, functional monomer, and carboxymethyl chitosan in step S3 is 25:8-12:0.5-1.5, and the volume fraction of acrylic acid in the mixed solution is 5-10%.

[0016] Since the crosslinking agent concentration directly affects the grafting rate and the crosslinking agent has a saturated concentration, the crosslinking agent is N,N'-methylenebisacrylamide, and the mass percentage of the crosslinking agent in the mixed solution is 0.25-0.75%.

[0017] Preferably, the pretreatment process of the fiber membrane material in step S3 is: ultrasonic cleaning with anhydrous ethanol and water in sequence, and drying, so as to obtain the fiber membrane material pretreated by ultrasonic cleaning, thereby removing impurities on the surface of the membrane material and increasing the roughness and active sites of the membrane surface.

[0018] Considering that the grafting rate increases with the increase of irradiation dose and tends to stabilize after the irradiation dose reaches a certain amount, the specific steps of the irradiation treatment in step S3 are: under a nitrogen atmosphere, set the irradiation energy to 160-200keV, the irradiation dose to 40-70kGy, the irradiation temperature to room temperature, and the irradiation time to 5min.

[0019] When preparing the functional monomers of the present invention, the quaternary ammonium salt groups introduced by the reaction have strong hydrophilicity and can attract water molecules into the membrane. Acrylic acid contains carboxyl groups, and carboxymethyl chitosan also has a large number of hydrophilic groups. These hydrophilic groups can form hydrogen bonds with water, which increases the water absorption capacity of the fiber membrane and thus enhances the swelling performance of the fiber membrane dressing. In addition, the large number of hydrophilic groups on the surface of the fiber membrane can also increase the surface energy of the membrane material surface, making it easier for water to spread on the membrane material surface, thereby improving the wettability of the fiber membrane dressing. Carboxymethyl chitosan, as a natural polymer material, has good film-forming properties and mechanical properties. It synergizes with the functional monomers and acrylic acid to form a three-dimensional network structure on the surface of the fiber membrane material through cross-linking polymerization, thereby enhancing the interaction between fibers and improving the mechanical properties of the fiber membrane dressing. In addition, the pyridine groups introduced by the reaction in the functional monomers can also enhance the interaction force inside the fiber membrane by hydrogen bonding, π-π stacking, etc., further improving the mechanical properties of the fiber membrane dressing. The quaternary ammonium salt and pyridine groups in the functional monomers have antibacterial activity. They can interact with bacterial cell membranes, disrupting their integrity and allowing intracellular substances to leak, thereby achieving an antibacterial effect. Carboxymethyl chitosan also has certain antibacterial properties, and synergistically with the functional monomers further enhances the antibacterial effect of the fiber membrane dressing. The pyridine groups and acrylate structures introduced into the functional monomers can interact with the lipid layer on the skin surface, increasing the affinity of the fiber membrane dressing with the skin. Carboxymethyl chitosan has good biocompatibility and promotes permeation. The affinity of the pyridine groups and acrylate structures with the skin lipid layer, combined with the permeation-promoting properties of carboxymethyl chitosan, further promotes the delivery of active drug molecules and significantly enhances the transdermal absorption capacity of the fiber membrane dressing.

[0020] The irradiated grafted modified fiber membrane dressing prepared using the above method, under electron beam irradiation conditions, can trigger free radical reactions, promoting cross-linking and polymerization on the fiber surface, thereby enhancing the overall performance of the fiber membrane. Furthermore, by controlling the energy of the electron beam, the fiber skeleton structure is not significantly damaged during irradiation, maintaining the fiber membrane's high loading rate and large specific surface area. The active pharmaceutical ingredient can be attached or embedded in the fiber network through physical adsorption or chemical bonding, and slowly released when needed, fully exerting its function.

[0021] The present invention utilizes a co-irradiation method to initiate a cross-linking polymerization reaction of functional monomers, acrylic acid, and carboxymethyl chitosan on the surface of the fiber membrane, forming a three-dimensional network structure. When this structure comes into contact with water, the hydrophilic groups in the network attract water molecules, allowing them to enter the network. At the same time, by controlling the process parameters and regulating the cross-linking density, the fiber membrane dressing has a high swelling capacity while maintaining structural stability. After irradiation grafting, a hydrophilic coating is formed on the surface of the membrane material, further improving the wettability of the fiber membrane dressing. This improvement helps the dressing better contact the skin surface and improves the comfort of use. In addition, the three-dimensional network structure formed on the surface of the fiber membrane can also enhance the mechanical properties of the fiber membrane dressing. The use of the cross-linking agent N,N'-methylenebisacrylamide further consolidates this network structure and improves the overall mechanical properties of the fiber membrane dressing. The irradiation grafting reaction forms a coating with a specific structure and properties on the surface of the fiber membrane material, optimizing the network structure and surface properties of the membrane material, facilitating the penetration of drugs or bioactive substances from the surface of the fiber membrane dressing into the skin tissue, and further improving the transdermal absorption performance of the dressing.

[0022] In summary, the present invention significantly improves the swelling properties, wettability, mechanical properties, antibacterial properties and transdermal absorption properties of the fiber membrane dressing through precise process control and synergistic effects between raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the SEM image of the fiber membrane material without grafting modification;

[0024] Figure 2 This is a SEM image of the fiber membrane dressing prepared in Example 1;

[0025] Figure 3 This is a SEM image of the fiber membrane dressing prepared in Example 2;

[0026] Figure 4 This is a SEM image of the fiber membrane dressing prepared in Example 3;

[0027] Figure 5 This is a SEM image of the fiber membrane dressing prepared in Example 4;

[0028] Figure 6 This is the SEM image of the fiber membrane dressing prepared in Comparative Example 3;

[0029] Figure 7 This is the contact angle test diagram of the fiber membrane dressing. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the embodiments described are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application. The raw materials used in the following examples are all common commercially available products.

[0031] Example 1

[0032] A method for preparing an irradiation-grafted modified fiber membrane dressing comprises the following steps:

[0033] Step S1: 3-chloro-2-hydroxypropyl methacrylate, N,N-dimethylformamide, and p-toluenesulfonic acid were mixed uniformly, the temperature was raised to 60° C. under stirring at 150 rpm, 4-pyridineacetic acid was added, the reaction was carried out for 8 h, and the mixture was naturally cooled to room temperature. Ethyl acetate and deionized water were added for extraction (the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate was 1:1:2). The organic phase was taken, the ethyl acetate was removed by rotary evaporation, and the mixture was vacuum dried at 60° C. for 12 h; wherein the molar ratio of the 3-chloro-2-hydroxypropyl methacrylate, p-toluenesulfonic acid, and 4-pyridineacetic acid was 1.1:0.015:0.9; and the mass volume ratio of the 3-chloro-2-hydroxypropyl methacrylate and N,N-dimethylformamide was 0.17 g / mL;

[0034] Step S2: Disperse the product obtained in step S1 into anhydrous ethanol under stirring at 150 rpm and nitrogen atmosphere, raise the temperature to 75°C, then add potassium iodide and triethylamine in sequence, reflux for 18 hours, naturally cool to room temperature, filter, take the filtrate, remove anhydrous ethanol by distillation under reduced pressure, then add ether and deionized water for extraction (the volume ratio of anhydrous ethanol, deionized water, and ether is 2:1:2), take the organic phase, remove the ether by rotary evaporation, and vacuum dry at 40°C for 24 hours to obtain a functional monomer; wherein the molar ratio of the product obtained in step S1, potassium iodide, and triethylamine is 0.9:0.25:1.3 (the amount of substance is calculated based on the given molecular weight of the target product); the amount of the product obtained in step S1 added to the anhydrous ethanol is 0.3 g / mL;

[0035] Step S3: At room temperature, carboxymethyl chitosan (active ingredient content 99%, purchased from Xi'an Tianzheng Pharmaceutical Excipients Co., Ltd.) was mixed evenly with deionized water and stirred for 50 minutes, and then acrylic acid, functional monomer, and cross-linking agent were added in sequence and stirred for 20 minutes to obtain a mixed solution; the pretreated fiber membrane material was immersed in the mixed solution, allowed to stand for 5 minutes, and then placed in an irradiation reaction system for irradiation treatment. After the irradiation was completed, the fiber membrane material was removed from the mixed solution, washed with deionized water for at least three times, and vacuum dried at 60°C. to constant weight, thereby obtaining the product; wherein, the mass ratio of the acrylic acid, the functional monomer, and the carboxymethyl chitosan is 25:10:1, the volume fraction of acrylic acid in the mixed solution is 7.5%, the cross-linking agent is N,N'-methylenebisacrylamide, and the mass percentage of the cross-linking agent in the mixed solution is 0.5%; the pretreatment process of the fiber membrane material is: ultrasonic cleaning with anhydrous ethanol and water in sequence, the ultrasonic power is 50W, the ultrasonic time is 5min, and vacuum drying is carried out at 60°C to constant weight. The fiber membrane material is a cellulose membrane material with a density of 30g / m 2 , with a thickness of 0.3 mm, purchased from Shanghai Wenfang Industrial Co., Ltd.; the specific steps of the irradiation treatment are: under a nitrogen atmosphere, according to a bath ratio of solution volume: membrane mass of 30, using electron beam irradiation (EBI) technology, setting the irradiation energy to 180 keV, the irradiation dose to 60 kGy, the irradiation temperature to room temperature, and the irradiation time to 5 min.

[0036] The grafting rate of the fiber membrane dressing prepared in this example was measured. First, a certain amount of fiber membrane sample was accurately weighed as the original sample, and its weight was recorded as W0. The fiber membrane was then subjected to irradiation grafting modification. After the reaction was complete, the fiber membrane was thoroughly washed and dried to remove unreacted substances and impurities. The grafted fiber membrane dressing was then accurately weighed again, and its weight was recorded as W1. The grafting rate was calculated using the formula: G (%) = (W1 - W0) / W0 × 100%. According to the above formula, the grafting rate of the fiber membrane dressing prepared in this example was 46.6%.

[0037] Example 2

[0038] A method for preparing an irradiation-grafted modified fiber membrane dressing comprises the following steps:

[0039] Step S1: 3-chloro-2-hydroxypropyl methacrylate, N,N-dimethylformamide, and p-toluenesulfonic acid were uniformly mixed, the temperature was raised to 65° C. under stirring at 150 rpm, 4-pyridineacetic acid was added, the reaction was carried out for 6 hours, and the mixture was naturally cooled to room temperature. Ethyl acetate and deionized water were added for extraction (the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate was 1:1:2). The organic phase was taken, the ethyl acetate was removed by rotary evaporation, and the mixture was vacuum dried at 60° C. for 12 hours; wherein the molar ratio of the 3-chloro-2-hydroxypropyl methacrylate, p-toluenesulfonic acid, and 4-pyridineacetic acid was 1.1:0.015:0.9; and the mass volume ratio of the 3-chloro-2-hydroxypropyl methacrylate and N,N-dimethylformamide was 0.17 g / mL;

[0040] Step S2: Disperse the product obtained in step S1 into anhydrous ethanol under stirring at 150 rpm and nitrogen atmosphere, raise the temperature to 80°C, then add potassium iodide and triethylamine in sequence, reflux for 15 hours, naturally cool to room temperature, filter, take the filtrate, remove anhydrous ethanol by distillation under reduced pressure, then add ether and deionized water for extraction (the volume ratio of anhydrous ethanol, deionized water, and ether is 2:1:2), take the organic phase, remove the ether by rotary evaporation, and vacuum dry at 40°C for 24 hours to obtain a functional monomer; wherein the molar ratio of the product obtained in step S1, potassium iodide, and triethylamine is 0.9:0.25:1.3 (the amount of substance is calculated based on the given molecular weight of the target product); the amount of the product obtained in step S1 added to the anhydrous ethanol is 0.3 g / mL;

[0041] Step S3: At room temperature, carboxymethyl chitosan (effective ingredient content 99%, purchased from Xi'an Tianzheng Pharmaceutical Excipients Co., Ltd.) was mixed evenly with deionized water and stirred for 40 minutes, and then acrylic acid, functional monomer, and cross-linking agent were added in sequence and stirred for 10 minutes to obtain a mixed solution; the pretreated fiber membrane material was immersed in the mixed solution, allowed to stand for 5 minutes, and then placed in an irradiation reaction system for irradiation treatment. After the irradiation was completed, the fiber membrane material was removed from the mixed solution, washed with deionized water for at least three times, and vacuum dried at 60°C. to constant weight, thereby obtaining the product; wherein, the mass ratio of the acrylic acid, the functional monomer, and the carboxymethyl chitosan is 25:10:1, the volume fraction of acrylic acid in the mixed solution is 7.5%, the cross-linking agent is N,N'-methylenebisacrylamide, and the mass percentage of the cross-linking agent in the mixed solution is 0.5%; the pretreatment process of the fiber membrane material is: ultrasonic cleaning with anhydrous ethanol and water in sequence, the ultrasonic power is 50W, the ultrasonic time is 5min, and vacuum drying is carried out at 60°C to constant weight. The fiber membrane material is a cellulose membrane material with a density of 30g / m 2, with a thickness of 0.3 mm, purchased from Shanghai Wenfang Industrial Co., Ltd.; the specific steps of the irradiation treatment are: under a nitrogen atmosphere, according to a bath ratio of solution volume: membrane mass of 30, using electron beam irradiation (EBI) technology, setting the irradiation energy to 200 keV, the irradiation dose to 70 kGy, the irradiation temperature to room temperature, and the irradiation time to 5 min; the grafting rate of the fiber membrane dressing prepared in this embodiment is 48.1%.

[0042] Example 3

[0043] A method for preparing an irradiation-grafted modified fiber membrane dressing comprises the following steps:

[0044] Step S1: 3-chloro-2-hydroxypropyl methacrylate, N,N-dimethylformamide, and p-toluenesulfonic acid were mixed uniformly, the temperature was raised to 55° C. under stirring at 150 rpm, 4-pyridineacetic acid was added, the reaction was carried out for 10 hours, and the mixture was naturally cooled to room temperature. Ethyl acetate and deionized water were added for extraction (the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate was 1:1:2). The organic phase was taken, the ethyl acetate was removed by rotary evaporation, and the mixture was vacuum dried at 60° C. for 12 hours; wherein the molar ratio of the 3-chloro-2-hydroxypropyl methacrylate, p-toluenesulfonic acid, and 4-pyridineacetic acid was 1.1:0.015:0.9; and the mass volume ratio of the 3-chloro-2-hydroxypropyl methacrylate and N,N-dimethylformamide was 0.17 g / mL;

[0045] Step S2: Disperse the product obtained in step S1 into anhydrous ethanol under stirring at 150 rpm and nitrogen atmosphere, raise the temperature to 70°C, then add potassium iodide and triethylamine in sequence, reflux for 20 hours, naturally cool to room temperature, filter, take the filtrate, remove anhydrous ethanol by distillation under reduced pressure, then add ether and deionized water for extraction (the volume ratio of anhydrous ethanol, deionized water, and ether is 2:1:2), take the organic phase, remove the ether by rotary evaporation, and vacuum dry at 40°C for 24 hours to obtain a functional monomer; wherein the molar ratio of the product obtained in step S1, potassium iodide, and triethylamine is 0.9:0.25:1.3 (the amount of substance is calculated based on the given molecular weight of the target product); the amount of the product obtained in step S1 added to the anhydrous ethanol is 0.3 g / mL;

[0046] Step S3: At room temperature, carboxymethyl chitosan (active ingredient content 99%, purchased from Xi'an Tianzheng Pharmaceutical Excipients Co., Ltd.) was mixed evenly with deionized water and stirred for 60 minutes, and then acrylic acid, functional monomer, and cross-linking agent were added in sequence and stirred for 30 minutes to obtain a mixed solution; the pretreated fiber membrane material was immersed in the mixed solution, allowed to stand for 5 minutes, and then placed in an irradiation reaction system for irradiation treatment. After the irradiation was completed, the fiber membrane material was removed from the mixed solution, washed with deionized water for at least three times, and vacuum dried at 60°C. to constant weight, thereby obtaining the product; wherein, the mass ratio of the acrylic acid, the functional monomer, and the carboxymethyl chitosan is 25:10:1, the volume fraction of acrylic acid in the mixed solution is 7.5%, the cross-linking agent is N,N'-methylenebisacrylamide, and the mass percentage of the cross-linking agent in the mixed solution is 0.5%; the pretreatment process of the fiber membrane material is: ultrasonic cleaning with anhydrous ethanol and water in sequence, the ultrasonic power is 50W, the ultrasonic time is 5min, and vacuum drying is carried out at 60°C to constant weight. The fiber membrane material is a cellulose membrane material with a density of 30g / m 2 , with a thickness of 0.3 mm, purchased from Shanghai Wenfang Industrial Co., Ltd.; the specific steps of the irradiation treatment are: under a nitrogen atmosphere, according to a bath ratio of solution volume: membrane mass of 30, using electron beam irradiation (EBI) technology, setting the irradiation energy to 160 keV, the irradiation dose to 40 kGy, the irradiation temperature to room temperature, and the irradiation time to 5 min; the grafting rate of the fiber membrane dressing prepared in this embodiment is 45.3%.

[0047] Example 4

[0048] A method for preparing an irradiation-grafted modified fiber membrane dressing comprises the following steps:

[0049] Step S1: 3-chloro-2-hydroxypropyl methacrylate, N,N-dimethylformamide, and p-toluenesulfonic acid were mixed uniformly, the temperature was raised to 60°C under stirring at 150 rpm, 4-pyridineacetic acid was added, the reaction was carried out for 8 hours, and the mixture was naturally cooled to room temperature. Ethyl acetate and deionized water were added for extraction (the volume ratio of N,N-dimethylformamide, deionized water, and ethyl acetate was 1:1:2). The organic phase was taken, the ethyl acetate was removed by rotary evaporation, and the mixture was vacuum dried at 60°C for 12 hours; wherein the molar ratio of the 3-chloro-2-hydroxypropyl methacrylate, p-toluenesulfonic acid, and 4-pyridineacetic acid was 1.1:0.02:1.0; and the mass volume ratio of the 3-chloro-2-hydroxypropyl methacrylate and N,N-dimethylformamide was 0.17 g / mL;

[0050] Step S2: Disperse the product obtained in step S1 into anhydrous ethanol under stirring at 150 rpm and a nitrogen atmosphere, raise the temperature to 75°C, then add potassium iodide and triethylamine in sequence, reflux for 18 hours, naturally cool to room temperature, filter, take the filtrate, remove anhydrous ethanol by distillation under reduced pressure, then add ether and deionized water for extraction (the volume ratio of anhydrous ethanol, deionized water, and ether is 2:1:2), take the organic phase, remove the ether by rotary evaporation, and vacuum dry at 40°C for 24 hours to obtain a functional monomer; wherein the molar ratio of the product obtained in step S1, potassium iodide, and triethylamine is 0.9:0.28:1.4 (the amount of substance is calculated based on the given molecular weight of the target product); the amount of the product obtained in step S1 added to the anhydrous ethanol is 0.3 g / mL;

[0051] Step S3: At room temperature, carboxymethyl chitosan (active ingredient content 99%, purchased from Xi'an Tianzheng Pharmaceutical Excipients Co., Ltd.) was mixed evenly with deionized water and stirred for 50 minutes, and then acrylic acid, functional monomer, and cross-linking agent were added in sequence, and the stirring was continued for 30 minutes to obtain a mixed solution; the pretreated fiber membrane material was immersed in the mixed solution, allowed to stand for 5 minutes, and then placed in an irradiation reaction system for irradiation treatment. After the irradiation was completed, the fiber membrane material was taken out from the mixed solution, washed with deionized water for at least three times, and vacuum dried at 60°C until Constant weight is obtained; wherein, the mass ratio of acrylic acid, functional monomer and carboxymethyl chitosan is 25:12:1.5, the volume fraction of acrylic acid in the mixed solution is 10%, the cross-linking agent is N,N'-methylenebisacrylamide, and the mass percentage of the cross-linking agent in the mixed solution is 0.75%; the pretreatment process of the fiber membrane material is: ultrasonic cleaning with anhydrous ethanol and water in sequence, the ultrasonic power is 50W, the ultrasonic time is 5min, and vacuum drying is carried out at 60°C to constant weight. The fiber membrane material is a cellulose membrane material with a density of 30g / m 2 , with a thickness of 0.3 mm, purchased from Shanghai Wenfang Industrial Co., Ltd.; the specific steps of the irradiation treatment are: under a nitrogen atmosphere, according to a bath ratio of solution volume: membrane mass of 30, using electron beam irradiation (EBI) technology, setting the irradiation energy to 190 keV, the irradiation dose to 50 kGy, the irradiation temperature to room temperature, and the irradiation time to 5 min; the grafting rate of the fiber membrane dressing prepared in this embodiment is 47.0%.

[0052] Comparative Example 1

[0053] A method for preparing an irradiation-grafted modified fiber membrane dressing is prepared according to the method described in Example 1, except that step S2 is omitted and the functional monomer in step S3 is replaced by the product obtained in step S1.

[0054] Comparative Example 2

[0055] A method for preparing an irradiation-grafted modified fiber membrane dressing is prepared according to the method described in Example 1, except that steps S1 and S2 are omitted and no functional monomer is added in step S3.

[0056] Comparative Example 3

[0057] A method for preparing an irradiation-grafted modified fiber membrane dressing is prepared according to the method described in Example 1, except that steps S1 and S2 are omitted, and no functional monomer or carboxymethyl chitosan is added in step S3.

[0058] Relevant performance tests were performed on the fiber membrane dressings prepared in Examples 1-4 and Comparative Examples 1-3.

[0059] The surface morphology of the fiber membrane and fiber membrane dressing was evaluated using a scanning electron microscope (SEM, Phenom G2 Pro, USA). The bulk film samples were coated with gold in a sputter coater (K575X Turbo Sputter Coater Sputtering System - Emitech) to prevent charging effects before testing. The results are shown in Figure 2. Figure 1-6 As shown, Figure 1 This is the SEM image of the fiber membrane material without grafting modification. Figure 2 This is the SEM image of the fiber membrane dressing prepared in Example 1. Figure 3 This is the SEM image of the fiber membrane dressing prepared in Example 2. Figure 4 This is the SEM image of the fiber membrane dressing prepared in Example 3. Figure 5 This is the SEM image of the fiber membrane dressing prepared in Example 4. Figure 6 The SEM image of the fiber membrane dressing prepared in Comparative Example 3. The results show that the image of the fiber membrane sample before grafting modification ( Figure 1 ) shows the shape of natural plant fibers, smooth surface, and network structure; the fiber membrane dressings prepared in Examples 1-4 and Comparative Example 3 ( Figure 2-6 The surfaces and gaps between the fibers were covered and filled with polymer molecules, which then cross-linked. The resulting polymer molecules clearly adhered to the fibers, indicating that under co-irradiation conditions, electron beam bombardment resulted in cross-linking and polymerization between the fibers and the acrylic acid, functional monomers, and other raw materials, without significantly damaging the fiber skeleton structure. While the fiber membrane dressing prepared in Comparative Example 3 maintained its corresponding reticular structure, its fiber surface became rough and even exhibited significant cracks.

[0060] The hydrophilicity and surface absorption capacity of the fiber membrane dressings prepared in Example 1 and Comparative Example 1 were evaluated using the WCA method. A drop shape analyzer (DSA30S, Kruss, Germany) was used to test the contact angle of the samples. The drop volume was 2 μL, and the test conditions were 25°C and 60% relative humidity. By measuring the contact angle of the liquid on the surface of the modified fiber membrane material, information such as the wettability of the droplet on the material surface can be obtained, thereby understanding the properties of the material surface. The results are shown in Figure 2. Figure 7 As shown, Figure 7 (a) is the water contact angle of the fiber membrane dressing prepared in Example 1. Figure 7 (b) is the water contact angle of the fiber membrane dressing surface prepared in Comparative Example 1. Figure 7 As can be seen, the surface contact angles of the fiber membrane dressings prepared in Example 1 and Comparative Example 1 were 42.0° and 59.7°, respectively. The fiber membrane dressing prepared in Example 1 had a lower surface contact angle, resulting in better wetting. This is because the introduction of quaternary ammonium salt groups into the copolymer molecules further increased the polarity of the fiber membrane dressing surface, thereby improving wettability.

[0061] Tensile testing was performed using an MTS (E43.104) electronic universal testing machine to examine the mechanical properties of the irradiated grafted modified fiber membrane dressing. For the tensile strength test, the entire film was cut into standard square specimens in the horizontal and vertical directions and tested at a rate of 3 mm / min. An extensometer (TST-1003) was used to record strain and stress until the maximum breaking strength was reached. Three replicates were performed for each test, and the average and standard deviation values ​​were obtained. By measuring the stress and strain data during the tensile process, the elastic modulus of the film can be calculated.

[0062] The swelling properties of the fiber membrane dressing were tested using a gravimetric method. The swelling effect of the sample in a PBS solution with a pH value of 7.4 was measured at room temperature. First, the prepared fiber membrane dressing was cut into 5cm×5cm sizes and dried in an oven at 30°C to constant weight. Then, it was immersed in a PBS solution. The swollen fiber membrane material was taken out of the PBS at different time intervals, and the surface moisture of the material was gently wiped dry with filter paper. It was then weighed until the maximum swelling rate was reached (about 24h). The swelling rate (S R ,%) is expressed as the increase relative to the initial mass of the sample, and the relevant formula is as follows: S R (%) = (m1-m0) / m0×100%; where m0 is the initial mass of the sample and m1 is the mass of the sample after swelling.

[0063] The present application selected representative Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) and adopted the plate count method to determine the antibacterial activity of the prepared fiber membrane dressing.

[0064] Catechin was dissolved in 75% ethanol aqueous solution (the mass volume ratio of catechin to 75% ethanol aqueous solution was 20 mg / mL) to prepare a catechin solution, and then a fiber membrane dressing (size 2 cm×2 cm) was immersed in the catechin solution and allowed to stand for 24 hours (the ratio of the volume of the catechin solution to the mass of cellulose was 30). The dressing was taken out, the concentration of catechin in the remaining catechin solution was determined, and the mass of the remaining catechin was calculated. The drug loading rate of the fiber membrane dressing was calculated based on the change in the mass of catechin before and after soaking the fiber membrane dressing. The soaked fiber membrane dressing was applied to the isolated skin surface of rats of equal area for an in vitro transdermal absorption experiment. A transdermal diffusion tester was used, PBS solution with a pH value of 7.4 was used as the receiving solution, the test temperature was 36.5°C, and after the test time of 24 hours, an appropriate amount of the receiving solution was taken to measure the catechin concentration, and an equal amount of fresh PBS buffer was promptly replenished to calculate the penetration rate.

[0065] The results of mechanical properties test, swelling properties test, antibacterial properties, drug loading rate, and transdermal absorption test are shown in Table 1. The above experiments were repeated three times, and the data were expressed as mean values. The data were statistically analyzed using Excel 2023 and SPSS26.0 software.

[0066] Table 1 Fiber membrane dressing performance test results

[0067]

[0068]

[0069] As can be seen from Table 1, the longitudinal elastic modulus of the fiber membrane dressings prepared in Examples 1-4 and Comparative Examples 1-3 is higher than the transverse elastic modulus; the fiber membrane dressings prepared in Examples 1-4 all exhibit excellent mechanical properties, wherein the longitudinal elastic modulus is between 726.0 MPa and 819.2 MPa, and the transverse elastic modulus is between 638.7 MPa and 726.9 MPa, while the mechanical properties of the fiber membrane dressings prepared in Comparative Examples 2-3 are relatively poor, wherein the mechanical properties of the fiber membrane dressing prepared in Comparative Example 3 are the worst, with a longitudinal elastic modulus of only 516.2 MPa and a transverse elastic modulus of only 403.0 MPa. As can be seen from the data of Comparative Examples 1-3, grafting acrylic acid and carboxymethyl chitosan onto the surface of the fiber membrane can effectively improve the mechanical properties of the fiber membrane dressing, and introducing a pyridine group into the functional monomer, and compounding the functional monomer with acrylic acid and carboxymethyl chitosan, and utilizing a three-dimensional network structure, π-π stacking effect, etc., can significantly improve the mechanical properties of the fiber membrane dressing. From the swelling rate test results, it can be seen that the maximum swelling rates of the fiber membrane dressings prepared in Examples 1-4 all reached more than 893%, among which the fiber membrane dressing prepared in Example 2 had the highest maximum swelling rate of 1077%, but after swelling, its surface became rough and uneven, resulting in poor skin feel; the maximum swelling rate of the fiber membrane dressing prepared in Example 1 was 924%, and the maximum swelling rate of the fiber membrane dressing prepared in Comparative Example 1 was 763%. By comparison, it was found that the quaternary ammonium salt group introduced in the functional monomer can synergize with acrylic acid and carboxymethyl chitosan to significantly improve the swelling properties of the fiber membrane dressing, which is also consistent with the water contact angle on the surface of the fiber membrane dressing. From the antibacterial performance test, it can be seen that the antibacterial activity of the fiber membrane dressings prepared in Examples 1-4 against Escherichia coli is above 99.6%, and the antibacterial activity against Staphylococcus aureus is above 98.5%, while the antibacterial activity of the fiber membrane dressings prepared in Comparative Examples 1-3 against Escherichia coli is 90.2%, 81.4%, and 66.3%, respectively, and the antibacterial activity against Staphylococcus aureus is 88.9%, 78.0%, and 64.1%, respectively. The above results show that the grafting of carboxymethyl chitosan and pyridine groups on the fiber membrane surface can improve the antibacterial performance of the membrane dressing to a certain extent, and the quaternary ammonium salt group, pyridine group, and carboxymethyl chitosan can synergistically enhance the antibacterial performance of the fiber membrane dressing. It can be seen from the drug loading rate test data that compared with Comparative Example 3, the drug loading rate of the fiber membrane dressings prepared in Examples 1-4 is slightly reduced, but still maintains a high level. The results of the transdermal absorption test show that the penetration rate of the fiber membrane dressings prepared in Examples 1-4 and Comparative Example 1 is significantly higher than that of Comparative Examples 2-3. The data of Comparative Examples 1-3 show that the introduction of pyridine groups and acrylate groups in the functional monomers can work together with carboxymethyl chitosan to significantly enhance the transdermal absorption capacity of the fiber membrane dressing by utilizing skin affinity and penetration-promoting properties.

[0070] Although the embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an irradiation-grafted modified fiber membrane dressing, characterized in that: The following steps are involved: Step S1: 3-chloro-2-hydroxypropyl methacrylate, N,N-dimethylformamide, and p-toluenesulfonic acid are uniformly mixed, the temperature is raised to 55-65° C. under stirring, and 4-pyridineacetic acid is added. The mixture is reacted for 6-10 hours, cooled to room temperature, and the organic phase is extracted, the extraction solvent is removed, and the mixture is dried; Step S2: Disperse the product obtained in step S1 in anhydrous ethanol under nitrogen atmosphere and stirring, raise the temperature to 70-80°C, add potassium iodide and triethylamine, react for 15-20 hours, cool to room temperature, and purify to obtain a functional monomer; Step S3: at room temperature, mix carboxymethyl chitosan and deionized water evenly, stir for 40-60 minutes, then add acrylic acid, functional monomer, and crosslinking agent in sequence, and continue stirring for 10-30 minutes to obtain a mixed solution; immerse the pretreated fiber membrane material in the mixed solution, and then irradiate the solution to obtain the product.

2. The method for preparing the radiation-grafted modified fiber membrane dressing according to claim 1, characterized in that: The molar ratio of 3-chloro-2-hydroxypropyl methacrylate, p-toluenesulfonic acid, and 4-pyridineacetic acid in step S1 is 1.1:0.01-0.02:0.8-1.

0.

3. The method for preparing the radiation-grafted modified fiber membrane dressing according to claim 1, characterized in that: The mass volume ratio of 3-chloro-2-hydroxypropyl methacrylate and N,N-dimethylformamide in step S1 is 0.15-0.20 g / mL.

4. The method for preparing the radiation-grafted modified fiber membrane dressing according to claim 1, characterized in that: In step S2, the molar ratio of the product obtained in step S1, potassium iodide, and triethylamine is 0.9:0.22-0.28:1.2-1.

4.

5. The method for preparing the radiation-grafted modified fiber membrane dressing according to claim 1, characterized in that: The amount of the product obtained in step S1 added to the anhydrous ethanol in step S2 is 0.2-0.4 g / mL.

6. The method for preparing the radiation-grafted modified fiber membrane dressing according to claim 1, characterized in that: In step S3, the mass ratio of acrylic acid, functional monomer, and carboxymethyl chitosan is 25:8-12:0.5-1.5, and the volume fraction of acrylic acid in the mixed solution is 5-10%.

7. The method for preparing the radiation-grafted modified fiber membrane dressing according to claim 1, characterized in that: The cross-linking agent in step S3 is N,N'-methylenebisacrylamide, and the mass percentage of the cross-linking agent in the mixed solution is 0.25-0.75%.

8. The method for preparing the radiation-grafted modified fiber membrane dressing according to claim 1, characterized in that: The pretreatment process of the fiber membrane material in step S3 is: ultrasonic cleaning with anhydrous ethanol and water in sequence, and drying.

9. The method for preparing the radiation-grafted modified fiber membrane dressing according to claim 1, characterized in that: The specific steps of the irradiation treatment in step S3 are: in a nitrogen atmosphere, setting the irradiation energy to 160-200 keV and the irradiation dose to 40-70 kGy.

10. An irradiation grafted modified fiber membrane dressing prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for modifying irradiation of polyethylene hollow fiber microporous membrane

    CN102649029A

  • Preparation method of bacterial cellulose-based long-acting micro-organism-preventing wound dressing

    CN110038151A

  • Composite wound dressing, preparation method and application

    CN115177778A

  • No title available

    GB1304112A

  • Wound healing dressings and formulations and methods of use thereof

    US20240358744A1